A promiscuous T cell epitope-based HIV vaccine providing redundant population coverage of the HLA class II elicits broad, polyfunctional T cell responses in nonhuman primates. Issue 2 (21st January 2022) - Ribeiro, Susan Pereira; De Moura Mattaraia, Vania Gomes; Almeida, Rafael Ribeiro; Valentine, Elizabeth Juliana Ghiuro; Sales, Natiely Silva; Ferreira, Luís Carlos S.; Sa-Rocha, Luiz Carlos; Jacintho, Lucas Cauê; Santana, Vinicius Canato; Sidney, John; Sette, Alessandro; Rosa, Daniela Santoro; et al.
Abstract: Over the last few decades, several emerging or reemerging viral diseases with no readily available vaccines have ravaged the world. A platform to fastly generate vaccines inducing potent and durable neutralizing antibody and T cell responses is sorely needed. Bioinformatically identified epitope-based vaccines can focus on immunodominant T cell epitopes and induce more potent immune responses than a whole antigen vaccine and may be deployed more rapidly and less costly than whole-gene vaccines. Increasing evidence has shown the importance of the CD4+ T cell response in protection against HIV and other viral infections. The previously described DNA vaccine HIVBr18 encodes 18 conserved, promiscuous epitopes binding to multiple HLA-DR-binding HIV epitopes amply recognized by HIV-1-infected patients. HIVBr18 elicited broad, polyfunctional, and durable CD4 +  and CD8+ T cell responses in BALB/c and mice transgenic to HLA class II alleles, showing cross-species promiscuity. To fully delineate the promiscuity of the HLA class II vaccine epitopes, we assessed their binding to 34 human class II (HLA-DR, DQ, and -DP) molecules, and immunized nonhuman primates. Results ascertained redundant 100% coverage of the human population for multiple peptides. We then immunized Rhesus macaques with HIVBr18 under in vivo electroporation. The immunization induced strong, predominantly polyfunctional CD4+ T cell responses in all animals to 13 out of the 18 epitopes; T cells from each animal recognized 7–11 epitopes. Our results provide a preliminary proof of concept that immunization with a vaccine encoding epitopes with high and redundant coverage of the human population can elicit potent T cell responses to multiple epitopes, across species and MHC barriers. This approach may facilitate the rapid deployment of immunogens eliciting cellular immunity against emerging infectious diseases, such as COVID-19.